The stock status of the pelagic fishes in Banyuasin coastal waters, Indonesia - Fauziyah, .; Putri, Wike Ayu Eka; Purwiyanto, Anna Ida Sunaryo; Agustriani, Fitri; Ermatita, .; Putra, Apriansyah (Journal of Fisheries, 2020)
Information on the condition of pelagic fish stocks in Banyuasin coastal waters is currently very limited. This study aimed to estimate the stock status of Auxis spp., Scomberomorus commerson, Selaroides leptolepis and Rastrelliger spp. based on the time series catch and effort data from 2008 to 2016 in the Banyuasin coastal waters, South Sumatra Province, Indonesia. All seven surplus production models, model performance, and fish stocks status were estimated. In order to determine the best-fitted model, several indicators of model performance were required. The Pella and Tomlinson model was the best-fitted model for S. commerson while the best-fitted model for Rastrelliger spp., Auxis spp. and S. leptolepis was the Fox model. The optimum effort (EMSY) value for S. commerson, Rastrelliger spp., Auxis spp. and S. leptolepis were 68677, 18226, 23402 and 22403 trips respectively. The maximum sustainable catch (CMSY) value for S. commerson, Rastrelliger spp., Auxis spp. and S. leptolepis were 1845, 515, 286, 667 tons respectively. In 2016 the stock of S. commerson was in recovery condition whereas it was subjected to overfishing for Auxis spp. and depleted for S. leptolepis and Rastrelliger spp.